Western nursery practice - Vinall, Henry N. (My University, 1903)
Introduction: I. Location. The chief point in choosing a location for a nursery is to secure the proper soil, and in this matter it is well to remember that all classes of fruit trees do not require the same kind of soil. In growing the apple, it is of paramount importance to plant the grafts on the best soil obtainable so that a strong healthy growth will be made high enough the first year to produce when headed back the body or trunk of you future tree. If two seasons are required for this growth, the tree is apt to be crooked when the second season’s growth commenced. Old nurserymen often avoid such result by cutting the first year’s growth back to the ground, if is too weak, and allowing the extra strength of the root produced by the previous season’s growth to be used in the production of this single shoot or whip; the prime object in growing apple trees for market, being to secure as large and stocky a tree as possible when it is two years old. With peach trees such is not the case, they as a rule attain to a marketable size in one year from the bud and there is a tendency to make too large a growth and nurserymen have found it advantageous to plant the seed on rather thin soil instead of rich loam, thus checking their growth and making their wood more hard and firm. With this exception however it is generally advisable to procure as good soil as possible and it should always be deep and . Never try to grow nursery stock over underlying hardpan. The best soil is a deep, rich, nearly level upland loam. II. Preparation of the Ground. This is an important consideration in the success of nursery work since in taking the crop of trees from the field it is often left in very poor condition for planting.
Citation: Vinall, Henry N. Western nursery practice. Senior thesis, Kansas State Agricultural College, 1903.
Morse Department of Special Collections
Keywords: United States; Spanish Relations; Cuban History; West Indian Commerce; Cuban Revolt; Theses